2020
DOI: 10.1177/2050157920959106
|View full text |Cite
|
Sign up to set email alerts
|

Mobile data donations: Assessing self-report accuracy and sample biases with the iOS Screen Time function

Abstract: With digital communication increasingly shifting to mobile devices, communication research needs to explore ways to retrieve, process, and analyze digital trace data on people’s most personal devices. This study presents a new methodological approach, mobile data donations, in which smartphone usage data is collected unobtrusively with the help of mobile log data. The iOS Screen Time function is used as a test case for gathering log data with the help of screenshots. The study investigates the feasibility of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 37 publications
4
103
0
Order By: Relevance
“…Our findings, however, indicate only a modest association between self-reports and usage logs, leading us to conclude that self-report measures of media use may not be a valid stand-in for more objective measures. Notwithstanding the potential biases affecting log-data 5,35,39,40 , if these measures are taken to be a valid reflection of actual usage 5,21,32,41,85 , our findings raise important concerns about the validity of findings and conclusions across many areas of the social sciences in which self-reported media use is a central outcome or explanatory variable.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our findings, however, indicate only a modest association between self-reports and usage logs, leading us to conclude that self-report measures of media use may not be a valid stand-in for more objective measures. Notwithstanding the potential biases affecting log-data 5,35,39,40 , if these measures are taken to be a valid reflection of actual usage 5,21,32,41,85 , our findings raise important concerns about the validity of findings and conclusions across many areas of the social sciences in which self-reported media use is a central outcome or explanatory variable.…”
Section: Discussionmentioning
confidence: 85%
“…These data suggest that self-reported and logged measures, rather than simply serving as different ways to measure media use, may in fact capture distinct constructs 31,38 . Log-based techniques, although they are not without their own biases 5,35,39,40 , provide a more direct, and likely more accurate measure of media use than self-report 5,21,32,41 . As such, there exists a need to systematically assess whether self-reported media use is an accurate indicator of actual usage patterns.…”
mentioning
confidence: 99%
“…We found slightly more accurate and valid estimates for adolescents who only used social media via their phones, but these estimates were not strikingly different for adolescents who used both the phone-and web-based applications. Future studies should extend our study by comparing different sources of objective digital trace data with each other (e.g., iOS screen time data or social media archival data donations) (Boeschoten, Van Driel, Oberski, & Pouwels, 2020;Ohme, Araujo, de Vreese, & Piotrowski, 2020).…”
Section: Strengths Limitations and Future Researchmentioning
confidence: 99%
“…Data are self-reported which may raise concerns regarding accuracy. Regarding screen time, research has found individuals tend to underreport their smartphone usage and factors such as short-term exposure, inconsistent usage, and multi-tasking can affect accurate recall of time spent on a given device ( Ohme et al, 2020 , Vanden Abeele et al, 2013 ) Research on self-report for substance use has been mixed. While studies have found that up to a quarter of respondents’ self-reports are not corroborated by urinalysis, other studies have found that accuracy of self-report data can be enhanced by implementing specific methodology ( Williams and Nowatzki, 2005 ).…”
Section: Limitationsmentioning
confidence: 99%